2015
DOI: 10.1177/1744629515576610
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary investigation into the effectiveness of a group-delivered sleep management intervention for parents of children with intellectual disabilities

Abstract: Abbreviated title: A sleep management group for parents of children with intellectual disabilities AcknowledgementsWe would like to thank all the families who took the time to complete our research questionnaires. Without their support this research would not have been possible. The views expressed are the authors' and do not necessarily reflect those of the funder. Funding acknowledgementsThe research reported here was commissioned by the Centre for Excellence and Outcomes (C4EO) with funding from the Departm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 30 publications
2
10
0
6
Order By: Relevance
“…(). However, take‐up was found to be high for a British sleep course aimed at parents of children with learning disabilities (Stuttard, Beresford, Clarke, Beecham, & Curtis, ). It may be the case that parents of children with learning disabilities are more likely to attend educational classes than parents of typically developing children.…”
Section: Discussionmentioning
confidence: 99%
“…(). However, take‐up was found to be high for a British sleep course aimed at parents of children with learning disabilities (Stuttard, Beresford, Clarke, Beecham, & Curtis, ). It may be the case that parents of children with learning disabilities are more likely to attend educational classes than parents of typically developing children.…”
Section: Discussionmentioning
confidence: 99%
“…Training group of parents in behavioral approaches to manage sleep problems represents a novel behavioral approach: Stuttard et al. (Stuttard, Beresford, Clarke, Beecham, & Curtis, ) reported the findings from a preliminary evaluation of a group‐delivered intervention routinely delivered by a Child and Adolescent Mental Health Service Learning Disability team in England: parents ( n = 23) of children with intellectual disabilities were recruited and the follow‐up was of 6 months. No parent dropped out and statistically significant improvements in night wakings, parent‐set goals, and parents’ sense of efficacy were observed.…”
Section: Treatment Of Chronic Insomnia In Neurodevelopmental Disabilimentioning
confidence: 99%
“…Clearly, the involvement of parents as agents for changing problematic sleep behaviors is fundamental; cognitive-behavioral techniques involving parents have been shown to be effective in improving significantly quality of life and well-being of patients and caregivers (Grigg-Damberger & Ralls, 2013;Jan et al, 2008). Training group of parents in behavioral approaches to manage sleep problems represents a novel behavioral approach: Stuttard et al (Stuttard, Beresford, Clarke, Beecham, & Curtis, 2015) reported the findings from a preliminary evaluation of a group-delivered intervention routinely delivered by a Child and Adolescent Mental Health Service Learning Disability team in England: parents (n = 23) of children with intellectual disabilities were recruited and the follow-up was of 6 months. No parent dropped out and statistically significant improvements in night wakings, parent-set goals, and parents' sense of efficacy were observed.…”
Section: Nonpharmacological Treatmentmentioning
confidence: 99%
“…Após leitura exaustiva dos resumos, foram excluídos todos os materiais que se encontravam em duplicidade, bem como os que não pertenciam à temática do estudo. Assim, restaram 16 artigos [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] para serem analisados em maior profundidade. O fluxograma da seleção dos estudos para a revisão integrativa é representado na Figura 1.…”
Section: Metodologiaunclassified
“…O estudo revelou que o sono da criança foi melhorando se comparado ao período pré-intervenção. Observou-se uma diminuição nos despertares noturnos e melhora na resistência a dormir 15 .…”
Section: Categoria 1: Avaliação Do Sono Em Crianças Com Doenças Crônicasunclassified